MULTILINGUAL PUBLICATION AS A LEGITIMATE TOOL TO INCREASE ACCESS TO SCIENCE (English translated version) - Aragón-Vargas, Luis Fernando (Pensar en Movimiento: Revista de Ciencias del Ejercicio y la Salud, 2014)
Duplicate publication, including the submission or publication of the same manuscript in two or more languages, is considered scientific misconduct. Meanwhile, properly conducted multilingual publication has been an exception difficult to deal with, rather than part of the normal scientific publishing process. While publication of a manuscript in a second or third language should not receive the same credit as the original publication, it should not be punished. Provided the appropriate disclosures and preliminary steps are taken, it should be highly encouraged instead, as it will enhance scientific communication and may reduce the knowledge gap around the world. Different types of multilingual publications are summarized and some basic guidelines are offered for the sanctioned publication of the same paper in multiple languages. ALSO AVAILABLE IN SPANISH AND PORTUGUESE FROM THIS JOURNAL.